Interpretation of Family Members’ Involvement in Religious Groups - Abidin, Kurniati (Society, 2020)
Family reactions and assessments of all family members towards family members belonging to specific religious groups still occur. This interpretation can trigger disharmony in the family and is an interesting social phenomenon to research. This research uses a qualitative research method. This research assumes that empirical realities occur in a socio-cultural context that is interrelated with one another. This research aims to describe family reactions, family social relationships, and family assessments on their family members’ involvement in specific religious groups. The informants were selected using a purposive sampling technique by taking three people from each religious group (Jamaah Tabligh, Wahdah Islamiyah, and Lembaga Dakwah Islam Indonesia known as LDII). Data were collected using in-depth interviews, observation, and documentation. The data analysis used in this research is descriptive qualitative. The results showed that family social relations on family members’ involvement in certain religious groups tended to get the same reaction based on their interpretation. Contravention interpretation from dominant family on family members belonging to specific religious groups still occurs compared with accommodative relationships. Meanwhile, family assessments on their family members’ involvement in certain religious groups are generally negative.